The effect of using some medicinal plants in the treatment of pain and inflammation in Abdali farms in the State of Kuwait - Alsarawi, Enas Abdulaziz (Journal of medical and pharmaceutical sciences, 2023)
Distinguishes Geographical location itself by it position and the influence of a climate contributed on the diversity of vegetable especially medicinal plant that own clear therapeutic benefits. The questionnaire was distributed among three segments of society (Herbal shops, Farmers, Consumer) with a total of 30 cases. The study shows that most of the community are heading to treatment with alternative medicine and their confidence in pain and infections recovery, as we got to know on many of plants and medicinal plants that are trading from the common people of the region. Medicinal plants have a major role in the province on biodiversity, it also has many benefits, it is a botanical wealth, also it is an economic wealth. The study dealt with methods for the different divisions of medicinal plants to facilitate the search process for the desired plant based on alphabetical based on the first letter from the scientific name, plant genetics, used part, medicinal effect, chemical composition for effective material, planting date, commercially. We got from the study some medicinal plants and herbs that are used by individuals in the area (mint, Coriandrum sativum, Cordia myxa) and the different ways to be used, areas and precautions for use, and due conditions achieved in treatment, and know the different taking of medications. Questionnaire has been restricted by schedule and column chart.